Methods of yeast genome editing - A. S. Rozanov; V. N. Shlyahtun; L. A. Tekutieva; O. M. Son; S. V. Sizova; S. E. Peltek (Вавиловский журнал генетики и селекции, 2018)
Yeasts are a convenient model eukaryote used for genome studies and genome editing. Saccharomyces cerevisiae is the species most widely employed in biotechnology, since it is easily cultivated in bioreactors and is absolutely safe. The last decade saw a significant development of methods of yeast genetic engineering and the creation of novel instruments adapted from other fields, which allowed one to significantly accelerate the construction of new strains. The most prominent examples are the proteins used for directed DNA editing. For a long time, yeast genome engineering was based on the yeasts’ system of homologous recombination. It was sufficient for several decades before the development of highthroughput methods. Many highthroughput methods were developed in the second decade of the XXI century, including those used in genomics, transcriptomics, proteomics, metabolomics, interactomics, etc. Modern bioinformatic databases now allow one to rapidly process the increasing flow of information and model cellular processes. As a result, the rate of analysis and prediction of targets for genome editing is currently higher than the rate of genome editing, which led to the development of new methods of genetic engineering. This process was particularly pronounced for microorganisms. Modern tasks require tens, hundreds, sometimes even thousands of genome modifications, which made researchers to look for new techniques. As a result, the instruments used for more complex objects, such as animals, plants, and cell lines, were adapted for yeasts. Modern methods for yeast genome editing allow introducing several modifications into the genome in a single step. In this study, we review the methods of directed genome editing and their applications and perspectives for yeasts.